Predictive values of ultrasound-based scoring system in morbidly adherent placenta for high risk group - Ali, Abd El-Naser Abd El-Gaber; Mohammad, Ahmed AM.; Khodry, Mustafa M.; Abdallah, Khaled M.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to find out the predictive values of an ultrasound-based scoring system in diagnosis of morbidly adherent placenta (MAP) for high risk group. Obstetrics and Gynecology Department, Faculty of Medicine, South Valley University, Egypt. Methods: 63 full term pregnant women (≥37 weeks of gestation) with high risk of morbidly adherent placenta underwent elective cesarean section. Placental assessment by 2 D ultrasound based on ultrasound scoring system in morbidly adherent placenta, these data were recorded for further comparison with intraoperative data for degree of placental adherence. Results: Incidence of MAP was 7.93% (4.76% had a focal form and 3.17% had a complete form of accreta). As regarding to scoring system, 82.5 of cases had a low risk (< 5), 9.5% had a moderate risk (6-7) and 7.93% had a high risk (8-12) of development of morbidly adherent placenta with p value <0.0001. The sensitivity, specificity, positive and negative predictive values of the US scoring system for morbidly adherent placenta were (92.3%, 94.1%, 87.453% and 98.2%) respectively. Conclusions: Ultrasound based scoring system had a high predictive value (sensitivity, specificity, positive and negative predictive values) in diagnosis of morbidly adherent placenta for pregnant women have any risk factors for developing MAP.